Carbon and nitrogen flow, and trophic relationships, among the cultured species in an integrated multi‑trophic aquaculture (IMTA) bay - T Mahmood (Inter-Research, 2016)
Stable isotopic signatures of organic carbon (δ13C) and total nitrogen (δ15N) were measured on suspended particulates and sediments in order to understand the sources of organic matter (OM), water quality and flow of organic carbon and nitrogen among integrated multi-trophic aquaculture (IMTA) species, as well as to evaluate the role of IMTA practice in accumulation and assimilation of OM during wet and dry seasons. OM distribution and composition were studied during 2011 in Sanggou Bay (SGB) of northern China, a system that receives terrestrial and oceanic inputs, and which is used for IMTA ventures. Results showed that higher terrestrial input of OM occurs during the wet compared to the dry season in the SGB. OM in suspended particulates (POM) showed marine- and terrestrial-derived signatures during the wet season, as revealed from their ranges in δ13C (-27.4 to -20.7‰) and δ15N (4.7 to 9.4‰). Sedimentary organic matter (SOM) showed signatures of marine-derived OM during both seasons, with ranges in δ13C and δ15N of -22.4 to -21.4‰ and 1.7 to 6.4‰, respectively. Shellfish and combined (shellfish, seaweed) cultures in SGB have the potential to reduce OM received from the fish cages as well as from the seasonal inputs from rivers. Mixing with Yellow Sea water, combined with prevailing circulation, favours the dispersal, dilution and transformation of OM and maintains and improves water quality. Based on our results, and compared with previous studies, the water quality of the SGB is likely to be sustained by IMTA activities.